2019
DOI: 10.5751/ace-01304-140102
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs relating to grassland and forest mine reclamation approaches in the central Appalachian region and implications for the songbird community

Abstract: Surface mining in the Appalachian region (USA) converts large areas of mature forest to early successional habitat. This shift in landscape structure has the potential to reduce habitat availability and suitability for forest-dwelling songbirds by reducing and fragmenting mature forest, but also to increase habitat availability for grassland-and shrubland-associated songbirds. We examined the influence of mountaintop mining/valley fill (MTMVF) reclamation habitats (grassland, shrubland, and remnant forest) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The complex ecosystem associated with mature woodland has yet to become established. However, elsewhere, mosaic and shrub-land habitats have proved best for increasing, at least, songbird diversity on reclaimed coal lands [70]. Here, results from mammal surveys suggest increases in diversity, numbers, and the length of food chains, while the bird seed fall work, which also suggests increasing populations and ecosystem productivity, demonstrates how forestation has significantly increased seed fall and so accelerated recolonisation of the site by local tree species.…”
Section: Discussionmentioning
confidence: 70%
“…The complex ecosystem associated with mature woodland has yet to become established. However, elsewhere, mosaic and shrub-land habitats have proved best for increasing, at least, songbird diversity on reclaimed coal lands [70]. Here, results from mammal surveys suggest increases in diversity, numbers, and the length of food chains, while the bird seed fall work, which also suggests increasing populations and ecosystem productivity, demonstrates how forestation has significantly increased seed fall and so accelerated recolonisation of the site by local tree species.…”
Section: Discussionmentioning
confidence: 70%
“…Knowledge on the adaptability of different plant species and their role in nutrient dynamics is vital to indulge in restoration measures through biological means (Gairola 2014). Margenau et al (2019) suggested plantation of native plant species accelerates the forest succession on degraded mined lands. The restoration of the degraded mine sites includes the control of all types of disturbances of soil, i.e., physical, chemical, and biological.…”
Section: Significance Of Soil Restorationmentioning
confidence: 99%
“…The observation that CNPs enhanced the seedling vigor index indicates that these seeds have enhanced capacity to be able to germinate, get establish, and survive under a range of challenging or stressful environmental conditions. This means that CNPs have the potential to enhance the vigor of native boreal forest seeds during propagation to facilitate plant growth under varied environments and may have applications in boreal forest restoration or reclamation programs [7,8,12].…”
Section: Effect Of Carbon Nanoparticles In Enhancing Seedling Vigormentioning
confidence: 99%
“…[6]. Natural resource extraction companies, for instance oil and gas companies, are mandated by law to return the ecologically important disturbed sites back to a functional upland boreal forest ecosystem, using native plant species [6][7][8]. Buffaloberry (Shepherdia canadensis L.) is a small shrub of the genus Shepherdia that produce edible berries.…”
Section: Introductionmentioning
confidence: 99%